GAMBARAN ANGKA KEJADIAN KOMPLIKASI PASCA ANESTESI SPINAL PADA PASIEN SEKSIO SESARIA - Hayati, Mardhiyah; Sikumbang, Kenangan Marwan; Husairi, Ahmad (Fakultas Kedokteran Universitas Lambung Mangkurat, 2015)
The spinal anesthesia is mostly used for cesarean section. The use of spinal anesthesia may cause the complications during and after surgery. The purpose of the research was to describe the incidence complications after spinal anesthesia on the first and third day after cesarean section in Ulin Hospital Banjarmasin. The method of the research is descriptive. The data were obtained from the medical records of the patient and questionnaire sheets. The sampling was used in consecutive sampling with the total of research subjects are 47 patients. The result of the research showed the incidence complications on the first day after spinal anesthesia is back pain 19(42.3%), nausea and vomit 6(13.4%), and headache 1(2.2%). The third day after spinal anesthesia is back pain 5(11%), nausea and vomit 24.4%), and headache 1(2.2%). The conclusion of the research is the image of the incidence complications after spinal anesthesia on the first day and third day at Ulin Hospital Banjarmasin shows back pain as the most complaints.Â Keywords: complications after spinal anesthesia, spinal anesthesia, Ulin Hospital Banjarmasin.